Provisions for the termination of Maritime Employment Contracts and Their Effects in the Saudi Law: An Analytical Study - Leen Hameed Alharbi (International Journal of Law Research and Studies, 2025)
This study aims to analyze the provisions governing the termination of maritime employment contracts and their effects under Saudi law, as stipulated in both the Labor Law and the Commercial Maritime Law. The study reviews the concept, nature, and characteristics of the maritime employment contract, as well as the grounds for its termination, whether arising from the will of the parties or from external causes. It also examines the legal effects resulting from the contract’s termination, highlighting the differences between the general provisions and those specific to maritime labor. A major focus of this study is the discussion and analysis of the newly issued Maritime Employment Contract Regulation dated 10/10/1446 AH, particularly the provisions related to the subject of this research. The study adopts an analytical method in examining legal texts. Our study concluded with several findings, most notably: the recent amendments to the Labor Law introduced a new regulation organizing maritime employment contracts, approved on 10/10/1446 AH, which has been examined and analyzed in multiple aspects. Among the key recommendations reached is advising the Saudi legislator to delete the provisions in the Maritime Employment Contract Regulation that allow for considering the maritime employment contract as indefinite in duration, as this contradicts the legal provisions affirming its fixed-term nature or its linkage to a specific voyage or a number of voyages.